PARAMETERS OF EJACULATE IN OVERWEIGHT MEN IN KUZBASS - Антон Игоревич Лесников; Алексей Андреевич Шмелев; Алексей Геннадьевич Тришкин; Лилия Владиславовна Курганова; Константин Александрович Луговой; Алексей Дмитриевич Бушмакин; Галина Павловна Зуева; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Кира Борисовна Мозес; Елена Владимировна Золото (Медицина в Кузбассе, 2022)
Currently, the problem of excess weight, obesity in men should be considered as a separate factor affecting reproductive function. Subfertile men have a higher body mass index (BMI) than the general population. Weight gain in men is associated with lower testosterone levels, poorer sperm quality, and reduced fertility compared to men of normal weight.